Social Community Characteristics Indigenous people in the Capital City of Nusantara, Indonesia - Rosalina Kumalawati; Astinana Yuliarti; Wisnu Putra Danarto; Inu Kencana Hadi; Jany Tri Raharjo; Rijanta Rijanta; Erlis Saputra; Ari Susanti (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
The planned relocation of Indonesia's national capital from Jakarta to East Kalimantan, particularly to Penajam Paser Utara and Kutai Kartanegara Regencies, is expected to substantially transform the region's social, economic, and cultural landscape. This study examined the baseline characteristics of local and indigenous communities within the Nusantara Capital City (IKN) development area, focusing on education, livelihoods, language, economic conditions, and land ownership. A mixed-method approach combining qualitative description and quantitative analysis was employed. Data were collected through documentation and surveys involving 200 purposively selected respondents from Sepaku, Pemaluan, Teluk Dalam, Babulu Darat, and Babulu Laut, all of whom had resided in the area for at least five years. The findings reveal a socioeconomically diverse community, with 45% of respondents completing senior high school and only 5% holding bachelor's degrees. Agriculture remains the dominant livelihood, employing 45% of respondents, while Indonesian serves as the primary lingua franca among Javanese, Bugis/Makassar, and indigenous Paser/Bali communities. Sepaku recorded the lowest average monthly expenditure (IDR 345,000), indicating limited purchasing power and potential vulnerability to marginalization. Emerging challenges include land ownership disputes, social tensions, theft, flooding, and limited access to clean water. These findings highlight the importance of culturally sensitive policies, community empowerment, and infrastructure development to ensure that indigenous and local communities benefit equitably from the IKN transformation.